The need to present a perfect body image: Development of a new measure of perfectionistic self-presentation - Ferreira, C. (2016)
Ferreira, C., Duarte, C., Pinto-Gouveia, J., & Lopes, C. (2016). The need to present a perfect body image: Development of a new measure of perfectionistic self-presentation. Current Psychology, 1-9. doi: 10.1007/s12144-016-9537-9.